Imam Lapeo Sebagai Pelopor Pembaharuan Islam di Mandar - Ruhiyat, Ruhiyat (Rihlah: Jurnal Sejarah dan Kebudayaan, 2015)
The purpose of this study is to explore and analyze the contribution of Imam Lapeo as a pioneer of Islamic reformer in Mandar. The result of this study has found that Imam Lapeo gave his life to ensure the reform of Islam in Mandar. Imam Lapeo got the support of local ruler and also support from society of Mandar. By those supports, Imam Lapeo could spread widely the concept of Islam from his mind. As we can see, right now in Lapeo Village, there are a lot of adherent of Imam Lapeo whom usually utilize the teaching of Imam Lapeo.